Relationships Between Biological Heavy Metals and Breast Cancer: A Systematic Review and Meta-Analysis - Liu, Lin; Chen, Jie; Liu, Chang; Luo, Yuxuan; Chen, Jiayun; Fu, Yuanyuan; Xu, Yajie; Wu, Haili; Li, Xue; Wang, Hui (Frontiers in Nutrition, 2022)
Introduction Heavy metals were classified as essential, probably essential, and potentially toxic in the general population. Until now, it has been reported inconsistently on the association between heavy metals and BC. In this meta-analysis, we aimed to assess the association between heavy metals and BC and review the potential mechanisms systematically. Methods We searched for epidemiological studies in English about the association between heavy metals and BC published before September 2020 in PubMed, Web of Science, and Embase databases. In total 36 studies, comprising 4,151 individuals from five continents around the world were identified and included. Results In all biological specimens, Cu, Cd, and Pb concentrations were higher, but Zn and Mn concentrations were lower in patients with BC than in non-BC participants [SMD (95% CIs): 0.62 (0.12, 1.12); 1.64 (0.76, 2.52); 2.03 (0.11, 3.95); −1.40 (−1.96, −0.85); −2.26 (−3.39, −1.13); p = 0.01, 0.0003, 0.04, <0.0001, <0.0001]. Specifically, higher plasma or serum Cu and Cd, as well as lower Zn and Mn, were found in cases [SMD (95% CIs): 0.98 (0.36, 1.60); 2.55 (1.16, 3.94); −1.53 (−2.28, −0.78); −2.40 (−3.69, −1.10); p = 0.002, 0.0003, <0.0001, 0.0003]; in hair, only lower Zn was observed [SMD (95% CIs): −2.12 (−3.55, −0.68); p = 0.0004]. Furthermore, the status of trace elements probably needs to be re-explored, particularly in BC. More prospective studies, randomized clinical trials, and specific pathogenic studies are needed to prevent BC. The main mechanisms underlying above-mentioned findings are comprehensively reviewed. Conclusion For BC, this review identified the current knowledge gaps which we currently have in understanding the impact of different heavy metals on BC. Systematic Review Registration www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020176934, identifier: CRD42020176934.